Controversies about extended-spectrum and AmpC beta-lactamases. - Thomson, K S (Centers for Disease Control and Prevention, 2001)
Many clinical laboratories have problems detecting extended-spectrum beta-lactamases (ESBLs) and plasmid-mediated AmpC beta-lactamases. Confusion exists about the importance of these resistance mechanisms, optimal test methods, and appropriate reporting conventions. Failure to detect these enzymes has contributed to their uncontrolled spread and sometimes to therapeutic failures. Although National Committee for Clinical Laboratory Standards recommendations exist for detecting ESBL- producing isolates of Escherichia coli and Klebsiella spp., no recommendations exist for detecting ESBLs in other organisms or for detecting plasmid-mediated AmpC beta-lactamases in any organisms. Clinical laboratories need to have adequate funding, equipment, and expertise to provide a rapid and clinically relevant antibiotic testing service in centers where these resistance mechanisms are encountered.